FOREIGNNESS IN TAN TWANG ENG'S THE GIFT OF RAIN - Mettia Indar Pratami; Tri Premesti (Universitas 17 Agustus 1945 Surabaya, 2019)
This research is an attempt to study Tan Twang Eng’s The Gift of Rain through the lense of Julia Kristeva’s concept of foreignness. The Gift of Rain exposes the story Philip Hutton, a half-Chinese and half-English young man who struggles to determine where he belongs to. The aims of this study is to investigate foreignness experienced by Philip and its impacts to Philip’s life. In additition, qualitative descriptive method is applied to analyze the topic. From the analysis of the protagonist, it is revealed that his sense of foreignness at home, religion as well as race emerge due to the death of his mother which leaves him to be the only Chinese in his English family. In addition, it is also influenced by the way others see and judge his multiple identities. Thus, living within two worlds−English and Chinese− makes Philip mistakenly believe that no one will accept him fully for he is just an outsider, belongs to nowhere. Keywords: Kristeva, foreignness, outsider